Institutions, interests, ideas and actors: An analysis of Pronacampo based on a cognitive approach - França, Damiana de Matos Costa; Farenzena, Nalú (Education Policy Analysis Archives, 2018)
The paper examines the construction of Programa Nacional de Educação do Campo [National Program of Rural Education] (Pronacampo) between 2011 and 2014. It analyzes the institutionalized ideas that originated Pronacampo, the actors and the interests involved, based on the cognitive approach of public policies analysis, with a greater approximation with Bruno Jobert and Ève Fouilleux’s perspective. It covers both the forum of ideas production, where the actors construct their ideas according to interests, institutions and power relations, and the forum of public policy communities, a space for organization and institutionalization of ideas. The study evidences that Pronacampo has differentiated references that reflect representations of distinct actors. Therefore, Pronacampo expresses a hybrid policy reference when aggregating opposite interests.